2016
DOI: 10.1186/s40634-016-0062-4
|View full text |Cite
|
Sign up to set email alerts
|

Three-dimensional kinematic and kinetic analysis of knee rotational stability in ACL-deficient patients during walking, running and pivoting

Abstract: BackgroundAnterior cruciate ligament (ACL) deficiency leads to altered stability of the knee. The purpose of this study was to compare the dynamic, rotational stability of the knee, expressed as rotational stiffness, between anterior cruciate ligament-deficient (ACLD) knees, their contralateral intact knees (ACLI) and a knee healthy control group during walking, running and 90° pivoting. We hypothesized a larger tibial internal rotation, a smaller knee joint external moment and a lower rotational stiffness in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 43 publications
1
10
0
Order By: Relevance
“…From studies comparing vertical jumps and cutting maneuvers, it is known that jumps evoke relatively low knee adduction/abduction moments compared to cutting maneuvers [15] or pivot tasks [16], so even the slightly increased knee adduction moments observed in the left leg during higher g-levels should not entail a significantly increased risk of injury. Similarly, the increase in knee internal rotation moments during centrifugation is comparable to the increase reported for cutting maneuvers compared to vertical jumps [15], and pivot tasks [17].…”
Section: Plos Onesupporting
confidence: 71%
“…From studies comparing vertical jumps and cutting maneuvers, it is known that jumps evoke relatively low knee adduction/abduction moments compared to cutting maneuvers [15] or pivot tasks [16], so even the slightly increased knee adduction moments observed in the left leg during higher g-levels should not entail a significantly increased risk of injury. Similarly, the increase in knee internal rotation moments during centrifugation is comparable to the increase reported for cutting maneuvers compared to vertical jumps [15], and pivot tasks [17].…”
Section: Plos Onesupporting
confidence: 71%
“…The difference may result from the running speed, in which the velocity of the control group is lower in this study, 2.33 m/s, compared to the author’s report of 4.24 m/s. The knee rotational moment was reported by some studies, which found a lower rotational moment in ACLD [ 8 ] and ACL reconstruction [ 27 ] knees compared to healthy limbs. The range of knee rotational moment for the control group compared favorably (0.07–0.13 Nm/(Bw × Bh) in [ 8 ] vs. 0.04–0.10 Nm/(Bw × Bh) in this study), and the peak value was similar to [ 27 ] when changing the unit to (body mass and leg length).…”
Section: Discussionmentioning
confidence: 98%
“…Some studies have found abnormal changes in ACLD [ 8 ] and reconstruction [ 3 , 6 , 7 ] knees during running. However, they did not report the alteration of contact forces, which is closely related to the development of osteoarthritis.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations